PENGARUH PENDEKATAN SAINTIFIK TERHADAP PRESTASI BELAJAR PKN DITINJAU DARI SIKAP DEMOKRASI SISWA KELAS V GUGUS I KECAMATAN ABANG - Ni Ketut Erna Muliastrini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
This study aims to determine the magnitude of the influence of the scientific approach to civics learning achievement in terms of students' democratic attitudes. This research is a quasiexperimental study with The Posttest-Only Control-Group Design. The study population was all students in class V of Elementary School I Class Abang District, totaling 147 students. A total of 100 students were selected as samples determined by the group random sampling technique. Data on democratic attitudes were collected by questionnaire and learning outcomes using multiple choice tests. Data were analyzed using Anava A-B analysis assisted by SPSS 17.00 for windows. The results showed that: First, there were differences in PKN learning achievement between students who took lessons with a scientific approach and students who studied with conventional learning models in class V students of Cluster I District Brother PKN learning achievement of students who take lessons with a scientific approach is better than PKN learning achievement of students who take lessons with conventional learning. Secondly, there is an interaction between the application of learning models and students' democratic attitudes towards PKN learning achievement in the fifth grade students of Cluster I of Abang District. For students who have high democratic attitudes, PKN learning achievement of students who take lessons with a scientific approach is better than conventional learning. Third, the learning outcomes of students who have high democratic attitudes who take lessons with a scientific approach are better than students who take lessons with conventional models. Kempat, for students who have low democratic attitudes, there is no difference in learning achievement between students who take lessons with a scientific approach and students who take lessons with conventional learning.